Evaluation of Chitosan Derivative Microparticles Encapsulating Superparamagnetic Iron Oxide and Doxorubicin as a pH-Sensitive Delivery Carrier in Hepatic Carcinoma Treatment: An in vitro Comparison Study - Bai, Meng-Yi; Tang, Sung-Ling; Chuang, Meng-Han; Wang, Ting-Ying; Hong, Po-da (Frontiers in Pharmacology, 2018)
We developed a novel, pH-sensitive drug delivery microparticle based on N-palmitoyl chitosan (NPCS) to transport the superparamagnetic iron oxide (SPIO) and anticancer drug doxorubicin (DOX). The characteristics of NPCS were characterized through nuclear magnetic resonance. Our results based on testing of volume swelling in multiple pH aqueous solutions revealed that the modified chitosan had a pH-sensitive property. The morphology and size of the DOX-SPIO/NPCS microparticles were investigated using transmission electron microscopy and scanning electron microscopy. The statistical result of microparticles had diameter of 185 ± 87 nm. Surface chemical moieties of DOX-SPIO/NPCS microparticles were confirmed using attenuated total reflection Fourier transform infrared spectroscopy and indicated the existence of mostly hydrophilic groups such as -OH, -C=O, and -C-O-C-. Transmission electron microscopy revealed the dark contrast of SPIO dots encapsulated in the NPCS matrix. Nuclear magnetic resonance T2-weighted magnetic resonance imaging confirmed that the produced DOX-SPIO/NPCS microparticles still exhibited T2 relaxation durations as short as 37.68 ± 8.69 ms (under administration of 2.5 μg/mL), which is comparable to the clinically required dosage. In the drug release profile, the DOX-SPIO/NPCS drug delivery microparticle was accelerated in an acidic environment (pH 6.5) compared with that in a basic environment. Microparticles in a cytotoxicity assay (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide assay) revealed that DOX-SPIO/NPCS microparticles had better antitumor ability than did free-form of DOX. Additionally, microparticles loaded with 0.5–5 μg/mL DOX in an acidic environment (pH 6.5) demonstrated higher efficacy against Hep G2 cell growth, possibly because of the swelling effect of NPCS, resulting in volume expansion and easy drug release. Accordingly, these large DOX-SPIO/NPCS microparticles showed potential for application as a pH-sensitive drug delivery system and as chemoembolization particles for hepatic carcinoma therapy.